2009
DOI: 10.1186/1465-9921-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant therapy with Cineole (Eucalyptole) reduces exacerbations in COPD: A placebo-controlled double-blind trial

Abstract: ISRCTN07600011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 20 publications
2
70
0
7
Order By: Relevance
“…In murine macrophages, Eucalyptus oil inhibited inducible nitric oxide synthase mRNA expression and NO production induced by lipopolysaccharide and IFN-γ [8]. Concomitant therapy of Eucalyptol reduced exacerbations and improves lung function in patients with COPD [9]. These findings support at least for some of the essential oils of Eucalyptus species used in the clinical treatment.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…In murine macrophages, Eucalyptus oil inhibited inducible nitric oxide synthase mRNA expression and NO production induced by lipopolysaccharide and IFN-γ [8]. Concomitant therapy of Eucalyptol reduced exacerbations and improves lung function in patients with COPD [9]. These findings support at least for some of the essential oils of Eucalyptus species used in the clinical treatment.…”
Section: Introductionsupporting
confidence: 67%
“…In accordance with this finding, our data supported the inhibition of mucus hypersecretion in COPD rats. Clinical trials have identified the benefit of concomitant therapy of cineol on improvement of lung function in patients with COPD [9]. Another placebo-controlled, double-blind trial also showed concomitant therapy using cineole improved lung function and health condition as well as to reduce dyspnea in asthma patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cineol konnte in einer placebokontrollierten COPD-Studie, in der es als Langzeittherapie zusätzlich zur medikamentösen Standardtherapie verabreicht wurde, die Exazerbationsrate im Vergleich zu Placebo signifikant senken [23].…”
Section: Pharmacotherapy Of Copdunclassified
“…(27) Likewise, Hodder et al (28) found that the LAMA-IC and LABA-IC combinations were superior to placebo in terms of improving pulmonary function (FEV 1 and FVC) during a six-month study involving patients with moderate or severe COPD, as determined by the GOLD classification. The effects that a mucolytic agent (29) and an antioxidant (N-acetylcysteine) (30) have on pulmonary function have been shown to be similar to that of placebo. The effect of PDE4 inhibitors on pulmonary function was shown to be superior to that of placebo.…”
Section: Pulmonary Functionmentioning
confidence: 99%